Financial Bootstrapping and Financial Literacy: The Moderating Role of Government Support on SME Performance - Parmitasari, Rika Dwi Ayu; Indriyani, Eka; Rusnawati, Rusnawati; Farild, Miftha; Efendi, Widya; Adawiah, Arabiatul (Jurnal Minds: Manajemen Ide dan Inspirasi, 2023)
SMEs can support long-term, stable, and sustainable economic development. However, funding, limited information, and lengthy credit administration procedures constantly severed their expansion. Potential solutions may emerge from external funding in creative and unconventional ways through financial bootstrapping. This study analyzes the influence of financial bootstrapping and financial literacy on SME performance using P2P lending in Makassar, Indonesia, with government support as mediation. Government support as mediation is expected to provide policies that facilitate SMEs obtaining external funding through fintech P2P lending to improve SMEs' business performance. This study employs a partial-least-squared structural-equation model (PLS-SEM) for data analysis of 220 businesses. The result shows that financial literacy significantly affects SME performance. This positive effect emerges in direct or mediated relationships. Financial bootstrapping does not substantially affect SME performance. This finding signifies the lack of information regarding the myriad of funding opportunities.